Uji Viabilitas dan Vigor Benih pada Beberapa Varietas Sorgum (Sorghum bicolor L.) dengan Umur Simpan yang Berbeda - Saputra, Dymas Iqbal; Widiastuti, Mira Landep; Azizah, Elia; Samaullah, M. Yamin (UNIVERSITAS LABUHANBATU, 2024)
Sorghum is an important food crop that be sustainable food needs and still has problems in the availability of quality seeds. The solution to improve the quality of sorghum seeds is by selecting superior varieties and appropriate storage periods during storage. This research aims to determine the viability and vigor of seeds in several varieties of sorghum (Sorghum bicolor L.) with different shelf lives. The method used is factorial RAL. The first factor is variety which consists of 3 levels used, namely Super 1 (V1), Numbu (V2), Suri 4 (V3). The second factor is shelf life which consists of 2 levels, namely shelf life 1 year (S1) and shelf life 2 years (S2). The effect of treatment is tested by analysis of variance and if the F test at the 5% level shows significant results, then proceed with the DMRT (Duncan Multiple Range) further test. The research results showed that there was an interaction between sorghum varieties and shelf life on the parameters of water content, normal sprout dry weight, electrical conductivity and there was no interaction on the parameters of germination, growth speed and vigor index. The best percentage for the observation variable was 9.17% water content, 17.79% dry weight of normal sprouts and 13.43% electrical conductivity in the Super 1 (V1) variety with a shelf life of one year (S1). Keywords: vigor, sorghum, shelf life, viability, seed quality